PENGARUH KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN PENDANAAN DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Mayandari, Gita; Jonathan, Aries (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to obtain an empirical evidence of institutional ownership, funding policy, firm size, cash holding, profitability, liquidity, capital structure and investment decision have an influence on firm value. Sample used in this research are all manufacturing companies listed in Indonesia Stock Exchange consistently during the period from 2017 until 2019. Sample selection method used was purposive sampling, there were 80 companies met the criteria, resulting 240 data are taken as sample. Research data were analyzed by doing hypothesis test using multiple regression method to determine the model of research.The result showed that firm size, profitability and investment desicion have an effect toward firm value. While five of the other independent variables there are institutional ownership, funding policy, cash holding, liquidity and capital structure do not have an effect on firm value.